User-centered design of crafts. The case of a commercial establishment (2019)
This article summarizes the development of BOHE academic project, based on Specialization Project Management Design and Innovation at Universidad Católica de Pereira; The aim was to identify the factors valued by tourists who buy crafts in a commercial establishment in Pereira, from user-centered design. The project designed a commercial establishment for artisan products, which represent the culture, tradition and identity, from technological and communication resources, providing efficient service.